Old Believer Population Distribution in Perm Province at the Turn of the 20th Century - Bakharev, Dmitry S. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2024)
This article studies the Old Believer population distribution in the Middle Urals in the late nineteenth — early twentieth centuries. The study refers to the 1890 Perm Province map, local published statistics and the results of the 1897 census. The primary methods employed in this study include cartography and the calculation of the mean settlement size. The spatial and quantitative analysis of the Old Believer population network shows its internal heterogeneity. It was divided into five clusters: eastern (Kamyshlov and Shadrinsk uyezds), central (Verkhoturye, Ekaterinburg, and Krasnoufimsk uyezds), northern (Cherdyn uyezd), western (Kungur, Okhansk, Perm, and Solikamsk uyezds), and the south-western (Osa uyezd). Some clusters included border volosts (subdistricts) of neighboring areas. All clusters touched the provincial border, i. e., they could have an interregional character. The central and western clusters were distinguished by a greater sparsity of the network of settlements compared to the others. The average size of Old Believer population generally repeated the characteristics of Orthodox settlements. In the central cluster, Old Believers preferred to live in zavods (factory settlements), in the eastern and south-western ones, in large villages, in the northern one, in small villages and hamlets, and in the western cluster, in tiny settlements, outposts, and single homesteads. Ekaterinburg was the only city fully included in the Old Believer settlement network. Accordingly, the Old Believers of the central cluster, being largely factory settlement and urban residents, are supposed to have differed significantly from their brothers in faith from other areas. Edinovertsy generally repeated the distribution of Old Believers, with a smaller scope and a tendency to live in larger settlements.